Characterization of Rabbit Nucleotide-Binding Oligomerization Domain 1 (NOD1) and the Role of NOD1 Signaling Pathway during Bacterial Infection - Guo, Mengjiao; Wu, Fahao; Zhang, Zhongfang; Hao, Guangen; Li, Rong; Li, Ning; Shang, Yingli; Wei, Liangmeng; Chai, Tongjie (Frontiers in Immunology, 2017)
Nucleotide-binding oligomerization domain 1 (NOD1) is the most prominent of all NOD-like receptors, which in the mammalian innate immune system, serve as intracellular receptors for pathogens and endogenous molecules during tissue injury. From rabbit kidney cells, we cloned rabbit NOD1 (rNOD1) and identified an N-terminal caspase activation and recruitment domain, a central NACHT domain, and C-terminal leucine-rich repeat domains. rNOD1 was expressed in all tested tissues; infection with Escherichia coli induced significantly higher expression in the spleen, liver, and kidney compared to other tissues. The overexpression of rNOD1 induced the expression of pro-inflammatory cytokines Il1b, Il6, Il8, Ifn-γ, and Tnf and defensins, including Defb124, Defb125, Defb128, Defb135, and Np5 via activation of the nuclear factor (NF)-κB pathway. Overexpression of rNOD1 inhibited the growth of E. coli, whereas knockdown of rNOD1 or inhibition of the NF-κB pathway promoted the growth of E. coli. rNOD1 colocalized with LC3, upregulated autophagy pathway protein LC3-Ⅱ, and increased autolysosome formation in RK-13 cells infected with E. coli. In summary, our results explain the primary signaling pathway and antibacterial ability of rNOD1, as well as the induction of autophagy that it mediates. Such findings suggest that NOD1 could contribute to therapeutic strategies such as targets of new vaccine adjuvants or drugs.